Kisah Sukses Usaha Kuliner Lokal(Studi Kasus UMKM Warasiko) - Helena Rosalia Parera; Elisabet Balu Vengi (Program Studi Manajemen Universitas Flores, 2025)
This research examines the success story of a local culinary business through a case study of Warasiko SME. The research focuses on identifying key success factors, business development strategies, as well as challenges and solutions faced in building a sustainable local culinary business. The research method employs a qualitative approach through in-depth interviews, field observations, and document analysis. The findings show that Warasiko's success is supported by several main factors: product innovation based on local wisdom, implementation of effective digital marketing strategies, quality consistency, and the ability to adapt to market changes. The findings of this research provide valuable insights for the development of other local culinary SMEs and can serve as a reference in formulating supportive policies for SMEs in the culinary sector.